Tingkat Kepatuhan Negara Anggota Uni Eropa Dalam Regulation On The Removal Of Fins Of Shark On Board Vessel - rahmi (Journal Social Politica, 2020)
The Council of Europe has adopted a regulation on the removal of fins of sharks on board vessels in 2003. The regulation prohibits eksploitation activities by shark finning, which cut the fins and take off the body thrown back into the sea. Member countries of the European Union expected to minimize activities that may result in shark populations are threatened with extinction by way of attempting to comply with these regulations. In executing and implementing the regulations, European Union member states have indicated a low level of compliance. Due to the vagueness and ambiguity of the regulation contained, then it is used as a basic for measuring the level of compliance. Some EU member states are states that do shark fishing in large enough quantities for export and import activities.